Psychological Contract Breach and Organizational Deviance Behaviour: Mediating Role of Professional Commitment - Bhattarai, Ganesh; Karki, Dipendra; Dahal, Rewan Kumar (Nepal Journal of Multidisciplinary Research, 2020)
This study was carried out to measure the direct impact of employees’ psychological contract breach on organizational deviance behavior and professional commitment, direct impact of professional commitment on organizational deviance behavior, and mediating role of professional commitment in the relationship between psychological contract breaches to organizational deviance behavior. As the respondents, 426 employees working in Nepalese non-profit making organization (i.e. international non-government organization working in Nepalas well as national level non-government organization) were surveyed. were drawn from the analysis of crosses sectional perceptual data adopting quantitative research method, deducting reasoning approach and positivist research philosophy. Regression analysis, after the confirmatory factor analysis, revealed that (a) employee’s psychological contract breach was positively associated with organizational deviance behavior, (b) employees psychological contract was negatively associated with professional commitment, (c) employees’ professional commitment was negatively associated with organizational deviance behavior, and (d) professional commitment mediated the relationship of psychological contract breach to organizational deviance behavior. Moreover, regarding effect size, the direct effect size of psychological contract breach to predict organizational deviance behavior was .86, and an indirect effect through professional commitment was -.12.Based on the study's conclusion, numbers of theoretical implication and practical implications are suggested.